The Gift of a Lifetime: The Hospital, Modern Medicine, and Mortality - Alex Hollingsworth; Krzysztof Karbownik; Melissa A. Thomasson; Anthony Wray (Center for Economic Studies and ifo Institute (CESifo), 2022)
The past century witnessed a dramatic improvement in public health, the rise of modern medicine, and the transformation of the hospital from a fringe institution to one essential to the practice of medicine. Despite the central role of medicine in contemporary society, little is known about how hospitals and modern medicine contributed to this health transition. In this paper, we explore how access to the hospital and modern medicine affects mortality. We do so by leveraging a combination of novel data and a unique quasi-experiment: a large-scale hospital modernization program introduced by The Duke Endowment in the early twentieth century. The Endowment helped communities build and expand hospitals, obtain state-of-the-art medical technology, attract qualified medical personnel, and refine management practices. We find that access to a Duke-supported hospital reduced infant mortality by 10%, saving one life for every 20,000 (2017 dollars) spent. Effects were larger for Black infants (16%) than for White infants (7%), implying a reduction in the Black-White infant mortality gap by one-third. We show that the effect of Duke support persisted into later life with a 9% reduction in mortality between the ages of 56 and 65. We further provide evidence on the mechanisms that enabled these effects, finding that Endowment-supported hospitals attracted higher-quality physicians and were better able to take advantage of new medical innovations.
Keywords: EI140; J13; N32; 330; modern medicine; hospitals; mortality; infant health; hospital funding; physician labor supply; medical innovation; health care complementarities; charitable giving